Deep Learning Feature Representation Applied to Cross Dataset Pedestrian Re-identification - Xie, Hongmei; Zhou, Yanggang; Liu, Qiang (International Journal of Computer Sciences and Engineering, 2025)
Pedestrian re-identification technology has become the current research focus due to its wide range of applications. This study conducted cross dataset pedestrian re-identification to solve the problem that the single dataset’s difficulty for simulating the actual situation and its poor generalization ability. Deep learning has made remarkable achievements in the fields of machine learning recently, so the deep learning technology is integrated into cross datasets pedestrian re-identification system. Here we improved the three-layer convolutional neural network (CNN) structure proposed by Yang Hu in Asia Conference on Computer Vision (ACCV), 2014. The Batch Normalization (BN) layer has been added to reduce the over-fitting degree during training period and the adjusted cosine similarity algorithm is used for pedestrian feature match to solve the defect of cosine similarity algorithm. Finally we implemented the entire cross dataset pedestrian re-identification system and got the experimental results. The Shinpuhkan2014dataset was chosen as training set. We compared the training results before and after adding BN layer and found that test accuracy increased, test loss decreased and over-fitting phenomenon eased. The VIPeR and i_LIDS datasets were chosen as test sets. We evaluated the effects on VIPeR and i_LIDS based on the CNN model that training on Shinpuhkan2014dataset. The cumulative matching rate rank5 increased by 1.7% on VIPeR dataset compared with the current level, the rank10 and rank20 also increased. And the cumulative matching rate rank1 increased by 1.8% on i_LIDS dataset compared with the current level, the rank5 and rank10 also increased.